Towards an analysis of the policies that shape public education: Setting the context for school leadership. (October 2015) - Bell, Les; Stevenson, Howard
The environment in which school leaders and teachers work is shaped by educational policy. Policy is, in turn, derived from the dominant political ideologies at any particular time. The interrelationship between ideology and policy shapes both the overall organization of education and the operational practices and procedures of staff in schools and colleges. An understanding of the nature of policy, how it is derived from political ideology and how policy helps to determine both the organization of education at national, local and school and college level can help school leaders to develop effective responses to policy and policy shifts. This article offers a model for conducting such an analysis.